Oxidation products of stigmasterol interfere with the action of the female sex hormone 17β-estradiol in cultured human breast and endometrium cell lines - Newill, Heike; Loske, Renate; Wagner, Jörg; Johannes, Christian; Lorenz, Reinhard L.; Lehmann, Leane (Molecular nutrition & food research, 2007)
Phytosterols are constituents of plant membranes and are thus contained in low concentrations in vegetable products as well as at high concentrations in functional food designed to reduce serum cholesterol levels. Similar to ChOL, phytosterols are oxidized chemically in food and by biotransformation in vivo. Although oxyphytosterols have been detected in the serum of healthy human subjects, little is known of their biological activity. Therefore, the estrogenic and antiestrogenic activities of a mixture of six oxidation products of stigmasterol (oxy‐StOL) were determined at the following endpoints: (i) the affinity to isolated human estrogen receptors (ER), (ii) the basal and 17β‐estradiol (E2)‐induced expression of the alkaline phosphatase (AlP) in human endometrial adenocarcinoma (Ishikawa) cells, and (iii) the basal and E2‐induced proliferation of human breast adenocarcinoma (MCF‐7) cells. Oxy‐StOL was able to replace E2 from human ERα and ERβ and induced a weak estrogenic response in MCF‐7 cells. Moreover, the E2‐induced activity of the AlP in Ishikawa cells as well as the E2‐induced proliferation of MCF‐7 cells were decreased at noncytotoxic concentrations (up to 10 μM), indicating that at least one component of oxy‐StOL represents an estrogen‐active compound which might interfere with endogenous estrogens.